(3efXheI aj GdUdGIs - (3eLghds
(3ChdgG (B:s
(3ajeG jLH HGdaQV ef GdUdGI , GdMeO ddg Ydi fhGdg hGdUdGI Ydi fHjg hBdg (B*** (3heG hLHJ HGdfPQ ddJfPQ JHY adjeJKd fG PQgG ceG hVY (B...s
(3BNQgG (B:s
...(3aCMeO Gddg bd MeOj hZf HPdJ aj GdKfGA LgOj (B*** (3eUdjG Ydi GdfHj hGdCdi Hge dfG GdOjf GdMfja GcJedGs
(3JHUQI GdeDda (B:s
(3HNW eZGjQ gh GdTGYQ UGdM GdLYHQj ef Bd cGTa GdZWGAs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis